Assessing the factorial validity and the internal reliability of the International Trauma Questionnaire (ITQ); PTSD and complex PTSD among survivors of sexual violence in Ireland. (17th June 2022) - Frost, R.; Vang, M. Lousion; Hyland, P.; Shevlin, M.; McCarthy, A.; Murphy, J.
Abstract: Aims: To assess the factorial validity and internal reliability of the International Trauma Questionnaire (ITQ) among a treatment-seeking sample of survivors of sexual violence in Ireland. In addition, to assess the diagnostic rate of post-traumatic stress disorder (PTSD) and complex post-traumatic stress disorder (CPTSD) among the samples. Methods: Participants were adult survivors of sexual violence ( N = 114) in receipt of therapeutic support at the Dublin Rape Crisis Centre. The ITQ was utilised to measure PTSD and CPTSD symptoms and confirmatory factor analysis was employed to assess the factorial validity of the ITQ. Composite reliability was employed to assess the internal reliability of the ITQ scale scores. Results: The confirmatory factor analysis results indicated that a six-factor correlated model and a two-factor higher model were good representations of the latent structure of the ITQ, both models are consistent with the conceptualisation of CPTSD. All ITQ subscales possessed satisfactory internal reliability except for the affective dysregulation subscale. Of the sample, 56.1% met the criteria for CPTSD and 20.2% met the criteria for PTSD. Conclusions: The ITQ captured a distinction between PTSD and CPTSD symptoms and produced reliable scores within the sample, but replication with a larger sample size is required. In addition, the study findings demonstrated that CPTSD was relatively common among those seeking psychological support following sexual violence.